Edukasi Pencegahan COVID-19 di Masyarakat Adat Pantai Kelating Kecamatan Tabanan - Putu Adi Cahya Dewi (Politeknik Kesehatan Kartini Bali, 2022)
The Covid-19 pandemic has had a major impact on society, especially the Balinese, who are thick with their traditions. Prevention of Covid-19 in Balinese communities needs to be done so that healthy conditions in the community during the pandemic are maintained. Research conducted by Ariyanti (2020) at Gadungan Village of Tabanan Bali shows that most people have implemented Covid-19 prevention behaviors well. However, it is still lacking in the implementation of regular disinfectants and sports activities. Better education is needed for the community, especially in Balinese to increase of activities to prevent the spread of Covid-19. The activity carried out was education on preventing Covid-19 for Balinese who were undergoing a ceremony to welcome the Nyepi day of Caka Year 1944 at Kelating Beach, Tabanan District, using leaflet media from the Ministry of Health. The target is Balinese who are present at Kelating Beach, Tabanan District. This is followed by a health check and the provision of masks, multivitamins, hand soap and hand sanitizer. After the Covid-19 prevention education was carried out, they committed to maintaining health protocols by: washing hands using soap and running water, using masks and hand sanitizers, maintaining distance and away from crowds, doing physical activity regularly and eating. nutritious food and also take a multivitamin.